An overview on reproductive isolation in Oryza sativa complex. Issue 6 (22nd November 2018) - Nadir, Sadia; Khan, Sehroon; Zhu, Qian; Henry, Doku; Wei, Li; Lee, Dong Sun; Chen, LiJuan
Abstract: Reproductive isolation is generally regarded as the essence of the speciation process. Studying closely related species is convenient for understanding the genetic basis of reproductive isolation. Therefore, the present review is restricted to the species and subspecies of the Oryza sativa complex, which includes the two domestic rice cultivars and six wild species. Although closely related, these rice species are separated from each other by a range reproductive barriers. This review presents a comprehensive understanding of the forces that shaped the formation of reproductive barriers among and between the species of the O. sativa complex. We suggest the possibility that domestication and artificial breeding in these rice species can lead to the early stages of speciation. Understanding the evolutionary and molecular mechanisms underlying reproductive isolation in rice will increase our knowledge in speciation and would also offer practical significance for the implementation of crop improvement strategies. Abstract : This review presents a comprehensive understanding of the forces that shaped the formation of reproductive barriers among and between the species of the Oryza sativa complex.